Analysis of the Characteristics of Solar Cell Array Based on MATLAB/Simulink in Solar Unmanned Aerial Vehicle - Haixin Wang; Jianxin Shen (IEEE Access, 2018)
In order to study the solar cell power system of solar unmanned aerial vehicle (UAV), this paper builds a simulation model of solar cell according to the solar cell mathematical model. The characteristic curves of solar cells are obtained by MATLAB/Simulink. The characteristic curves of the solar cells are compared by changing the solar intensity and the external temperature. At the same time, the ground test of the solar cell module is carried out. The corresponding conclusions are obtained by the ground test and simulation analysis. The solar cells have a certain maximum power point at any condition, which is great significant to study the maximum power tracking of solar cells in solar UAVs.